The Effect of Cash on Delivery and Online Customer Reviews on Purchase Decisions of Lazada Consumers in Majalengka Regency - Pipih Sopiyan; Dudung Abdullah; Alan Rusdiana; Deni Istiono; Nofa Auliyatul Faizah (Finance and Business Management Journal, 2024)
Communication is developing very rapidly. One of the greatest discoveries in the field of information and communication technology is the discovery of the internet. Currently, the majority of people tend to use technology to support their needs, one of which is that the internet can be used to do various things, including the development of digital technology and business competition which continues to innovate both in services. features and promotions to maintain its existence. The aim and objective of this research is to determine the influence of cash on delivery and online customer reviews on purchase decisions of Lazada consumers in Majalengka regency. The method used in this research is a descriptive and verification approach. The population of this research is Lazada consumers in Majalengka Regency whose exact number is not known. The sample was taken using a purposive sampling technique of 100 respondents. The data collection technique was carried out by filling out a questionnaire using Google Form which was distributed via the WahttsApp application. The data analysis technique uses multiple linear regression analysis accompanied by classical assumption tests, coefficient of determination tests, model feasibility tests (f tests), and t test hypothesis tests. The analysis results show that Cash on delivery and Online customer review have a significant influence on purchasing decisions.